A new species of the genus Hilethera Uvarov, 1923 (Orthoptera: Acrididae: Oedipodinae) from China and its complete mitochondrial genome - Dong, Jiajia; Chen, Zhenning; Wang, Qingqing; Guan, Delong; Xu, Shengquan; Robillard, Tony (Zootaxa, 2019)
The new species, Hilethera xinjiangensis sp. nov. (Orthoptera: Acrididae: Oedipodinae) is described based on specimens collected from Xinjiang, northern China. The new species is similar to H. brevipennis Zheng & Lu, 2002 and H. turanica Uvarov, 1925, but differs from: (1) dark brown in general coloration, (2) darker coloration in forewings, (3) forewings longer than H. brevipennis but shorter than H. turanica, (4) cubital area of forewings boarder than H. brevipennis and H. turanica, (5) hind tibiae dark brown with two light yellow pre-basal rings, while dark with one fade pre-basal ring in H. brevipennis and light yellow with three dark rings in H. turanica.In addition, the complete mitogenome of holotype was sequenced using next-generation sequencing technology. The total length of the assembled mitogenome is 16,145 bp, representing 13 protein-coding genes, 22 transfer RNA genes, two ribosomal RNA genes and one noncoding region (D-loop region). The new mitogenome sequence is compared with published Oedipodinae mitogenomes and the phylogenetic relationships within the subfamily are reconstructed. The results infer that the gene cox1 could be a useful marker for higher phylogenetic level, while the genes nd5 and rrnL could be potentially useful markers between closely related species.